Clinical evaluation of differences in proximal contact strength of various fixed dental prosthesis materials - N Gopi Chander; Arnob Biswas (Wolters Kluwer Medknow Publications, 2018)
Objective: The study compared the proximal contact strength (CS) of different fixed dental prosthesis (FDP) materials. Materials and Methods: Thirty volunteers participated in this study with definitive inclusion and exclusion criteria. Participants were divided into full metal, zirconia, and metal ceramic groups. The CS between the natural teeth and the maxillary posterior quadrant FDP was measured with force gauge. The data were evaluated with one-way analysis of variance test, and Tukey's honest significant difference post hoc was done to compare the mean values. Paired samples t-test was used to compare the mean values between pre- and postoperative CS. Results: The postoperative CS observed in the full metal group in premolar was 0.320 ± 0.1092 N and in second molar was 0.385 ± 0.1130 N. CS obtained with zirconia FDP in both premolar (0.679 ± 0.0927 N) and molar (0.770 ± 0.0960 N) was highest among all groups. The results were statistically significant (P < 0.001). Conclusion: Postoperative CS was greater in zirconia when compared with metal and metal ceramic FDP. Clinical Relevance: FDP materials had acceptable CS. Zirconia is preferable for optimal CS.